Influence of Fe2+ and Fe3+ on the Performance and Microbial Community Composition of a MFC Inoculated with Sulfate-Reducing Sludge and Acetate as Electron Donor - José Roberto González-Paz; María del Carmen Monterrubio–Badillo; Alberto Ordaz; E. Inés García-Peña; Claudia Guerrero-Barajas (Journal of Chemistry)
A sulfidogenic sludge supplemented with acetate was evaluated in the anodic chamber of microbial fuel cells (MFCs) in the presence of sulfate (SO4-2)/Fe3+ and sulfate (SO4-2)/Fe2+ to investigate the MFC performance and the effect of the iron ions on the composition of the microbial community since sulfate and iron ions are frequently present in wastewater derived from several anthropogenic activities. The current densities were up to 0.025 mA/cm2 and 0.017 mA/cm2 for MFCs with Fe2+ and Fe3+, respectively. Accordingly, the redox activity was slightly higher in the presence of Fe2+ than Fe3+. In general, the metabolic activity of the MFC supplemented with Fe2+ was higher than the system with Fe3+ reaching a percentage of sulfate reduction (% SR), sulfide concentration (mg/L HS-), and removal of chemical oxygen demand (% COD removal) of 35.2±0.75, 450.3±3.6, and 50.05±0.24 for % SR, HS-, and % COD, respectively, whereas in the MFC with Fe3+, the percentages were of 30.1±1.076, 220.6±2.0, and 11.78±10.81 for % SR, HS-, and % COD, respectively. The microbial population determined in each system was also correlated to the metabolic activity. Rhodospirillales, Caulobacterales, and Burkholderiales were the most abundant orders of bacteria in the MFC with Fe3+, whereas with Fe2+, Rhodobacterales, Sphingomonadales, and Rhizobiales. Desulfohalobiaceae and Desulfovibrionaceae were identified in the presence of Fe2+. Unexpected interactions and combinations of microorganisms were observed in a relatively short culturing time, demonstrating the importance of characterizing the anode biofilm prior to shifts in iron ion concentrations on a long-term basis.